The Influence of College Entrepreneurship Education System on the Cultivation of Applied Innovative Talents - Zhao, Xiaoqi; Wang, Xiaorong (Frontiers in Psychology, 2022)
With China’s socioeconomic development, especially in the educational sector, foreign advanced education experience might not be omnipotent for the innovation and entrepreneurship education (IEE) in Chinese colleges. In response to such a difficult context, firstly, this study was conducted to analyze the applied innovative talent cultivation status quo in Chinese colleges under innovation and entrepreneurship. Then, the authors dug into the current situation and the development of IEE-related courses in College S through Questionnaire Survey (QS) and unveiled the efficacy of entrepreneurship environment and conditions, IEE courses, teaching methods, and policy system on the college applied innovative talents cultivation. Finally, the experiment discovered that three problems are prominent when training applied innovative talents in College S: unreasonable talent training process, imperfect education system, and emphasizing theory over practice. The main reason is that the IEE courses are not systematically set up, and teachers are in severely short supply. According to the research outcomes, the corresponding countermeasures and suggestions were proposed for applied innovative talents cultivation in College S. It is concluded that the cultivation of applied innovative talents under innovation and entrepreneurship should be reformed from four aspects: educational concept, educational model, educational policy, and social support, laying a foundation for improving the quality of IEE in Chinese colleges and universities and strengthening the cultivation of applied innovative talents.